Certain Properties of The Result Involution Graph Related to The O’Nan Group - Dawood, Hayman Jassim; Aubad, Ali Abd (Iraqi Journal of Science, 2025)
The behavior of the result involution graph associated with the finite simple group O’N was investigated in this article. This includes determining particular properties of the graph and showing their effect on the algebraic properties of the group O’N.